METODE SKRINING STROKE LARGE VESSEL OCCLUSION (LVO) MENGGUNAKAN ASESMEN VISION, APHASIA, NEGLECT (VAN) - Andriyani; Habibi, Irbi Eki (Jurnal Sinaps, 2023)
Acute stroke is a sudden episode of stroke that can cause long-term motor disturbances and impair cognitive abilities in patients. Stroke is the leading cause of the highest disability and the second leading cause of death worldwide. Approximately 62% of stroke patients are ischemic stroke, and 24-46% of all ischemic stroke cases involve large vessel occlusion (LVO). LVO stroke is a condition that occurs due to blockage in the large blood vessels in the brain and has a poor prognosis. The management of LVO stroke depends greatly on time to achieve satisfactory results in patients. The screening method considered effective in LVO stroke cases is using the Vision, Aphasia, Neglect (VAN) assessment based on the clinical symptoms of the patient. This VAN assessment tests the cortical function of patients while still making motor function as the main symptom. Patients in the Positive VAN category have a sensitivity of 100%, specificity of 90%, a positive predictive value of 74%, and a negative predictive value of 100% to detect LVO stroke.